(untitled) (Fiep Bulletin - online, 2016)
The article aims to present as Physical Education in Brazil becomes part of the school curriculum. Also discussed about the use of technology in Physical Education classes, especially Educopédia platform created by the Municipal of Rio de Janeiro Education in 2010 in partnership with HI Futures order to help education professionals during their classes. Thus, to achieve the goal adopted the methodology of qualitative type of bibliographic nature. The results was that Physical Education, according to the studies found is the discipline that uses more Educopédia platform, although there is precarious structural conditions for access to the media instrument. The considerations are that Educopédia has proven to be of great potential mechanism in schools, however, the physical conditions still constitute a restriction on student access to the network.